Comparison of Biometric Formulae for Intra Ocular Lens Power Calculation: Doi: 10.36351/pjo.v40i1.1692 - Ghaffar, Mariam; Muneer Quraishy, Muhammad; Adnan Shaikh, Muhammad; Hussain, Mehvash; Sultan, Zaheer (Pakistan Journal of Ophthalmology, 2023)
Purpose: To determine the accuracy of different biometric formulae for intraocular lens power (IOL) calculation in predicting a target postoperative refraction within ± 1.0 diopters in patients with long axial length undergoing phacoemulsification. Study Design: Cross sectional study. Place and Duration of Study: Department of Ophthalmology and visual sciences, Unit 1 Dow University of Health Sciences, Dr. Ruth KM Phau Civil Hospital Karachi from February 2019 to August 2019. Methods: The study included 45 eyes with cataract and preoperative uncorrected visual acuity ranging from 6/60-6/12, axial length of 24.5 to 27.0 mm with no other ocular problem. IOL power was calculated with SRK-T, Holladay 1 and Haigis formula installed in optical biometer AL-Scan (Nidek Co, Ltd., Gamagori, Japan) and by Barrett universal 2 formula from http://www.apacrs.org/barrett_universal2/. Patients underwent phacoemulsification by single surgeon. Follow up included refractive status using Autorefractokertometer, URK-700 (Unicos Co., Ltd., Korea) at 6th week post-operatively. Deviation of actual postoperative refraction from the predicted target preoperative refraction were calculated and values within ± 1.0 diopter were considered accurate. Data was analyzed using SPSS version 22. Results: Outcome in terms of postoperative refractive error (+1D to -1D) with respect to biometric formula showed 100% accuracy using Haigis formula, 90% accuracy using SRK-T formula, 72.72% accuracy using Barrett universal II formula and 66.67% accuracy using Holladay-1 formula. Conclusion: Haigis formula proved to be more reliable and accurate than SRK-T, Holladay 1 and Barrett universal II formulae for calculation of intraocular lens power in eyes with long axial length.